Influence of Covid-19 on Surgical Practice: An update is a need - Sundas Javeed, Farid Ahmad Khan, Muhammad Awais, Ayesha Waheed, Rizwan Khan, Rooh-Ul-Ain, Komal Saeed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate existing practice recommendations in the event of a COVID-19 pandemic and to develop future pandemic strategies. Methods: In the context of COVID-19, a review of surgical societies' and government agencies' websites, as well as current literature, was done to discover recommendations for plastic surgery operations. Our plastic surgery problems have been divided into four areas, with guidelines developed for each. Results: This pandemic demands modification in clinical practice and transformations are recommended in outpatients and peri-operative settings to minimize the potential risk of disease transmission. Prioritization methods, operating room atmosphere, health care personnel safety, and preoperative patient evaluation are all covered by consensus standards for Plastic and Reconstructive Surgery. Operation theatre should be modified to minimize the disease transmission. PPE use is marked critical for all health care personals working in emergency settings. Preoperative assessment should be a critical component of management strategy. Conclusion: Since COVID-19 is predicted to resurface, doctors must weigh the risks and benefits of each operation in relation to essential patient care, COVID-19 spread reduction, and health-care worker safety. The plastic surgeon will be guided by scientific evidence-based standards that include conscious decision-making in emergency and non-urgent patients, OR changes, PPE usage, and preoperative screening tools.